Pentacoordinated silicon in the high-pressure modification of datolite, CaBSiO4(OH). Issue 7 (25th May 2018) - Gorelova, Liudmila A.; Pakhomova, Anna S.; Aprilis, Georgios; Dubrovinsky, Leonid S.; Krivovichev, Sergey V.
Abstract : A new modification of borosilicate datolite, CaBSiO4 (OH), has been discovered using synchrotron-based in situ high-pressure single-crystal X-ray diffraction. Abstract : A new modification of borosilicate datolite, CaBSiO4 (OH), has been discovered using synchrotron-based in situ high-pressure single-crystal X-ray diffraction. The phase transition from low (I) to high (II) pressure modification is isosymmetric and occurs between 27 and 33 GPa. The crystal structure of datolite-II contains pentacoordinated Si atoms forming SiO5 triangular bipyramids that share edges to form Si2 O8 dimers. The dimers are linked through BO4 tetrahedra, resulting in the [B(SiO4 )OH] 2− layers of a novel topology that has not previously been observed in inorganic compounds. Datolite-II is only the second inorganic structure that contains Si in purely fivefold coordination. The results obtained shed new light on the high-pressure behaviour of silicates and demonstrate that cold compression can be considered as a low-energy pathway to metastable structures, which might possess unusual and unexpected coordination geometries and topologies.